Modificação microestrutural da liga de magnésio AZ31 por fricção e mistura a altas velocidades - Valio, Gustavo Trindade (Universidade Federal de São Carlos, 2015)
Due to the current growth in the fossil fuels consumption, there is a great concern about the increase in pollutant emissions. In order to reduce these emissions, research indicates that the decrease in vehicle weight can be one of the solutions to reduce these gas emissions. One possible way to reduce the car weight is the replacement of parts that uses high density metals by Magnesium alloys. The major problem with this replacement is the lack of ductility that this material has at room temperature, being necessary to heat the plates before the conformation. This heating process has a high production costs and it is unfeasible to use in the automotive industry today. In view of this problem, this work aims to study this lack of conformity to room temperature using a microstructure modification technique located in the regions of conformation. The technic used was Friction Stir Processing (FSP) at high speed. This processing is similar to Friction Stir Welding (FSW), but without joining materials. The FSP is just a localized microstructural modification. The analysis performed in this study after processing at 1, 7 and 10 m/min show that the microstructure and mechanical properties undergoes various changes at for every processing speed output different. The results showed that the material after processing improves the ductility at room temperature as grain size decreases.
Microstructure modification by high speed friction stir processing of magnesium AZ31 alloy
Keywords: Processamento por fricção e mistura; FSP; Magnésio; Evolução microestrutural; Fluxo de material; Friction stir processing; Magnesium; Microstructural evolution; Material flow and ductility; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA